AN EVIDENCE-DRIVEN APPROACH TO SCRUM LAW MODIFICATIONS IN AMATEUR RUGBY PLAYED IN SOUTH AFRICA. Issue 7 (11th March 2014) - Hendricks, S; Micheal, L; James, B; Clint, R; Wayne, V
Abstract : Background: In 2012, the South African Rugby Union approved a new set of scrum Laws for amateur rugby, to be implemented at the start of the 2013 rugby season. These Law changes were based on the relatively high proportion of scrum-related catastrophic injury data collected as part of the BokSmart National Rugby Safety Programme over the preceding 4 years. Objective: Describe the scrum-related catastrophic injury data in South Africa between 2008–2012, and discuss how this evidence justified the change in the Amateur Scrum Laws. Design: Prospective. Setting: The South African amateur and professional rugby-playing population. Participants: Junior and Senior rugby-playing population within South Africa. Risk factor assessment: Independent variables included playing position, scrum injury mechanism, subjective comments relating to the cause of the injury, possession at the time of the scrum, coaching received on safe scrum techniques, surface footing at the time of the scrum. Main outcome measurements: Catastrophic head, neck and spinal injuries. These were classified into Acute Spinal Cord Injury (ASCI) or Traumatic Brain Injury (TBI). Results: The scrum accounted for 33% (n=20 of 60) of all catastrophic injuries between 2008 and 2012. Eighteen of the 20 scrum injuries (90%) were confirmed ASCIs, with 13 of these being permanent injuries. For the scrum injury mechanisms (n=19), 'impact on the engagement' was the most frequently reported (n=11 of 19, 58%), followed by "collapsed scrum" (n=7 of 19, 37%) and "popping out" (n=1 of 19, 5%). Conclusions: Based on these scrum-related catastrophic injury data, a change in the Amateur Scrum Laws of South African Rugby was justified. The purpose of these Scrum Law changes is to reduce the number of scrum-related catastrophic injuries by minimising impact injury and subsequent scrum collapse in amateur rugby in South Africa.